A Normative Juridical Analysis of Standard Clauses in E-commerce: Consumer Protection and the Nullity of Exoneration Clauses on the Shopee Marketplace under Indonesian Law No. 8/1999 - Siti Widya Umiyati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study undertakes a normative juridical analysis of standard clauses (klausula baku) employed by business actors (pelaku usaha) in online sale and purchase transactions (jual beli) conducted via the Shopee marketplace in Indonesia. Driven by the observed prevalence of unilateral contractual terms that disproportionately shift risk and responsibility to the consumer, the research assesses their compliance with the fundamental prohibitions established in Article 18 of Law No. 8 of 1999 Concerning Consumer Protection (UUPK). Utilizing a descriptive analytical approach based exclusively on secondary legal materials, the study confirms that common seller clauses specifically those disclaiming liability for shipping damage or manufacturing variance, and those refusing product returns or refunds directly contravene UUPK Article 18. These clauses are primarily in violation of points (1)(a), which prohibits the transfer of responsibility of the business actor, and (1)(b), concerning the refusal of returns. The central legal finding is that, pursuant to UUPK Article 18(3), these non-compliant contractual terms are declared null and void by law (batal demi hukum). This statutory nullity legally reinforces the business actor's mandatory liability (Article 19) and underscores the necessity for proactive supervision and intervention by the Business Dispute Resolution Agency (BPSK). The paper concludes with recommendations for strengthening platform governance and consumer legal literacy to ensure contractual balance and legal certainty within the rapidly evolving digital commerce ecosystem.